The television treasury : onscreen details from sitcoms, dramas and other scripted series, 1947-2019 - Terrace, Vincent, 1948- (McFarland & Company, Inc., Publishers, 2020)
""The first and only of its kind, this book is a straightforward listing of trivia facts from hundreds of TV series aired between 1947 and 2019. Organized by topic, trivia facts include everything from home addresses of characters, to names of pets and jobs that characters worked. Featured programs include popular shows like The Big Bang Theory and Friends and more obscure programs like A Date with Judy or My Friend Irma. Included is an alphabetical program index that lists trivia facts grouped by series."--Provided by publisher"--